Linking channel hydrology with riparian wetland accretion in tidal rivers. Issue 1 (14th January 2014) - Ensign, Scott H.; Noe, Gregory B.; Hupp, Cliff R.
Abstract [1] The hydrologic processes by which tide affects river channel and riparian morphology within the tidal freshwater zone are poorly understood yet are fundamental to predicting the fate of coastal rivers and wetlands as sea level rises. We investigated patterns of sediment accretion in riparian wetlands along the nontidal through oligohaline portion of two coastal plain rivers in Maryland, U.S., and how flow velocity, water level, and suspended sediment concentration (SSC) in the channel may have contributed to those patterns. Sediment accretion was measured over a 1 year period using artificial marker horizons, channel hydrology was measured over a 1 month period using acoustic Doppler current profilers, and SSC was predicted from acoustic backscatter. Riparian sediment accretion was lowest at the nontidal sites (mean and standard deviation = 8 ± 8 mm yr−1), highest at the upstream tidal freshwater forested wetlands (TFFW) (33 ± 28 mm yr−1), low at the midstream TFFW (12 ± 9 mm yr−1), and high at the oligohaline (fresh‐to‐brackish) marshes (19 ± 8 mm yr−1). Channel maximum flood and ebb velocity was twofold faster at the oligohaline than tidal freshwater zone on both tidal rivers, corresponding with the differences in in‐channel SSC: The oligohaline zone's SSC was more than double the tidal freshwater zone's and was greater than historical SSC at the nontidal gages. The tidal wave characteristics differed between rivers, leading to significantly greater in‐channel SSC during floodplain inundation in the weakly convergent than the strongly convergent tidal river. High sediment accretion at the upstream TFFW was likely due to high river discharge following a hurricane.